Análise da hidratação de sementes de Jequitibá-branco (Cariniana estrellensis (Raddi) Kuntze) via modelo difusivo associado a imagens de microtomografia computadorizada - Camargos Filho, Anselmo Nogueira de (Universidade Federal de São Carlos, 2022)
Jequitibá-branco (Cariniana estrellensis (Raddi) Kuntze) is an endangered native species of significant ecological and commercial importance. Aiming at improving germination conditions with a consequent impact on the quantity and quality of seedlings produced, the present study aimed to contribute to the analysis of the hydration process of these seeds through the interpretation of the diffusive model adjustments considering the constant and variable effective diffusivity associated with investigation by X-ray computed tomography (micro-CT) images. The hydration curves were performed at temperatures of 25°C, 35°C and 45°C. The diffusive model was satisfactorily fitted for both constant and variable effective diffusivity. The effective diffusivity values were considered low since this type of seed presents protective tissues against mechanical impacts. The analysis of diffusivity variations allowed the observation of the three hydration phases. The microtomography analyzes allowed the evaluation of the tissue density variation in the humidities 0.25 kg/kg, 0.37 kg/kg, 0.50 kg/kg, 0.62 kg/kg, 0.75 kg/kg. There were no variations in dimensions during the hydration process. The analysis of the micro-CT images showed that there is an evident preferential distribution of water in the reserve tissues that act as a barrier to protect the embryo against water impacts, proving to be a promising technique to be used in this type of study.
Analysis of the hydration of Jequitibá-branco (Cariniana estrellensis (Raddi) Kuntze) seeds via diffusion model associated with microtomography images
Keywords: Jequitibá-branco; Cinética de hidratação; Modelo difusivo; Micro-TC; ENGENHARIAS::ENGENHARIA QUIMICA